Connect With Your Audience! The Relational Labor of Connection - Baym, Nancy (The Communication Review, 2015)
The theme of Console-ing Passions this year is cultivating community, a topic about which I have had much to say in the context of fan practices. In my work on fans and soap operas (e.g. Baym, 2000) and independent Scandinavian music (e.g. Baymn, 2007), I showed how audiences appropriate the affordances of the internet in order to build communities based on shared practices and meanings. In this paper, I want to look at building ties from another vantage point by considering the kind of work that relating to these often, but not always, mediated communities and individuals entails. I mean this short talk to be provocative rather than exhaustive, a peek into a potential trajectory into media work for feminist media studies.